The Farmer’s Personal Hygiene Improvement Through the Use of Hand Soap Gel Extract of Acem Acem Leaf - Mahyuni, Eka Lestari; Harahap, Urip (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Pesticide exposure due to poor personal hygiene is very high because farmers generally contact soil, fertilizers, and pesticides which are synthetic chemicals that are harmful to health. The leaves of acem acem are a type of wild plant that is often used by farmers in Tanah Karo as a medium for cleaning hands after applying pesticides. Based on the results of laboratory tests, this leaf has properties as a pesticide cleaner so that it can be used to improve the personal hygiene of farmers. This activity is carried out by empowering the behaviour of washing hands using hand soap gel acem acem leaf extract. Farmers' awareness to improve personal hygiene begins with socialization and training provided as personal hygiene education to improve public health. Education accompanied by the movement of washing hands with hand soap gel acem acem leaf extract has given a positive contribution and appreciation and can increase the enthusiasm of farmers to improve public health.